Some Fixed-Point Theorems for Multivalued Monotone Mappings in Ordered Uniform Space - Turkoglu Duran; Binbasioglu Demet (Fixed Point Theory and Applications, 2011)
We use the order relation on uniform spaces defined by Altun and Imdad (2009) to prove some new fixed-point and coupled fixed-point theorems for multivalued monotone mappings in ordered uniform spaces.